Bipolar disorder comorbidity in patients with a primary diagnosis of OCD. (2nd January 2017) - Saraf, Gayatri; Paul, Imon; Viswanath, Biju; Narayanaswamy, Janardhanan C.; Math, Suresh Bada; Reddy, Y. C. Janardhan
Abstract: Objective: Bipolar disorder (BD) is considered to be a common comorbid condition in subjects with obsessive-compulsive disorder (OCD), but there is limited literature on the prevalence of BD and its clinical correlates in those with a primary diagnosis of OCD. Methods: We studied the prevalence of BD in a sample of consecutively registered outpatients attending a specialty OCD clinic in India over a period of 13 months. One hundred and seventy-one patients with a primary diagnosis of OCD were assessed systematically using structured and semi-structured instruments. Results: The prevalence of lifetime BD in OCD was 4%. The OCD + BD group had an episodic course of OCD and higher rate of lifetime suicide attempts. Conclusions: BD may not be as highly prevalent in OCD as reported in literature. Those with OCD seem to have only a marginally higher risk for developing BD than the general population. A diagnosis of BD seems to have a pathoplastic effect on the course of OCD. Patients with OCD-BD comorbidity have to be specifically assessed for suicide risk.